2017
DOI: 10.1186/s13068-017-0992-9
|View full text |Cite
|
Sign up to set email alerts
|

Production of C2–C4 diols from renewable bioresources: new metabolic pathways and metabolic engineering strategies

Abstract: C2–C4 diols classically derived from fossil resource are very important bulk chemicals which have been used in a wide range of areas, including solvents, fuels, polymers, cosmetics, and pharmaceuticals. Production of C2–C4 diols from renewable resources has received significant interest in consideration of the reducing fossil resource and the increasing environmental issues. While bioproduction of certain diols like 1,3-propanediol has been commercialized in recent years, biosynthesis of many other important C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
65
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(67 citation statements)
references
References 124 publications
(183 reference statements)
1
65
0
Order By: Relevance
“…Ethylene glycol is a highly important commodity chemical. However, there are no known natural pathways to directly synthesize ethylene glycol from carbohydrates [27]. In this study, it was shown that ethylene glycol can be produced by E. cloacae S1 using xylonic acid as the sole carbon source.…”
Section: Discussionmentioning
confidence: 89%
“…Ethylene glycol is a highly important commodity chemical. However, there are no known natural pathways to directly synthesize ethylene glycol from carbohydrates [27]. In this study, it was shown that ethylene glycol can be produced by E. cloacae S1 using xylonic acid as the sole carbon source.…”
Section: Discussionmentioning
confidence: 89%
“…Ethylene glycol is a highly important commodity chemical. However, there are no known natural pathways to directly synthesize ethylene glycol from carbohydrates [29,30]. In this study, it was shown that ethylene glycol can be produced by E. cloacae S1 using xylonic acid as the sole carbon source.…”
Section: Discussionmentioning
confidence: 90%
“…[1][2][3] In recent studies a set of chemical compounds have been identified that can serve as intermediates for bridging biological and chemical processes. [1][2][3] In recent studies a set of chemical compounds have been identified that can serve as intermediates for bridging biological and chemical processes.…”
Section: Introductionmentioning
confidence: 99%
“…The chemical industry currently undergoes a paradigm change and progress is achieved to replace fossil based resources by renewable ones. [1][2][3] In recent studies a set of chemical compounds have been identified that can serve as intermediates for bridging biological and chemical processes. 4,5 In the list of C4-compounds 1,4-butanediol (BDO) is listed which can serve as chemical synthon besides its direct application as alcohol monomer compound for polyester synthesis.…”
Section: Introductionmentioning
confidence: 99%